The Influence Of Discounts, The "Free Shipping" Tagline, And Shopping Lifestyle On Generation Z's Impulse Buying Decisions On Shopee E-Commerce In Bengkulu City - Purnama, Sindi Ade; Susena , Karona Cahya; Adjie , Dwi Nova (Journal of Law, Social Science, and Management Review, 2025)
This study aims to analyze the influence of promotions in the form of discounts, the tagline "Free Shipping", and Shopping Lifestyle on impulsive purchasing decisions of Generation Z Shopee users in Bengkulu City. The method used is quantitative with a questionnaire survey on 100 respondents aged 17–28 years who are active Shopee users and activate the ad notification feature. Data were analyzed through multiple linear regression using SPSS to test the partial and simultaneous effects of these variables. The regression results show that discounts and the tagline "Free Shipping" do not have a significant partial influence on impulsive purchasing decisions, but shopping lifestyle has a positive and significant influence and is a dominant factor in this behavior. Simultaneously, the third variable has a significant influence with a coefficient of determination of 0.823, which means that 82.3% of the variation in impulsive purchasing decisions can be explained by the influence of discounts, the tagline "Free Shipping", and shopping lifestyle, while the rest is influenced by other variables not studied. This study provides important insights for e-commerce players in designing effective marketing strategies, especially for the Generation Z target market.